Impact of Big Five personality traits on authentic leadership. Issue 2 (22nd December 2020) - Shahzad, Khurram; Raja, Usman; Hashmi, Syed Danial
Abstract : Purpose: The bulk of the current research on authentic leadership focuses on the examination of its consequences. Little attention has been paid to the predictors of authentic leadership. We examined how the Big Five personality traits can predict an authentic leadership style. Design/methodology/approach: Using multisource time-lagged data from 305 leader–subordinate dyads, we examined how the Big Five traits (extraversion, agreeableness, consciousness, openness to experience and neuroticism) are related to authentic leadership. While leader personality was measured through self-reports, we measured authentic leadership style through subordinate reported data. Findings: We found good support for the proposed hypotheses. While extraversion, agreeableness, conscientiousness and openness to experience were positively related to authentic leadership style, neuroticism was negatively related to it. Practical implications: The findings support the trait view of leadership, suggesting that the personality traits of a leader can predict his/her authentic leadership style. These findings hold promise for managers in that they can use personality inventories and tests in the selection and evaluation process to select and train potential authentic leaders. Originality/value: We proposed a unique idea and tested it using leader–subordinate dyadic data that are time-lagged to test our hypotheses.